Evaluation of toxic effects of benzophenone on histopathology of Labeo rohita - Maham Riaz; Sajid Abdullah; Mina Jamil; Amna Rasheed; Urwah Sheikh; Maham Fatima; Nimra Umer; Kaynat Aslam (Toxicology Reports)
Benzophenone (BP) is an organic ultraviolet (UV) filter widely used in sunscreens and personal care products. This compound enters aquatic ecosystems due to industrialization, wastewater treatment plants (WWTPs), and domestic effluents, poses serious threats to aquatic organisms, and is considered an emerging pollutant. This laboratory-based study assessed the 96-hour (h) median lethal concentrations (LC50) and sub-lethal effects of BP on the histology of the gills and muscles of Labeo rohita. Fish fingerlings of the same weight (48 ± 2 g) and length (5 ± 2 in.) were exposed to gradually increasing concentrations of BP (100 µg/L to 1000 µg/L) and their 96-h LC50 was determined as 612.822 ± 37.38 µg/L. To determine the sub-lethal effects, the fish were exposed to 1/5th of the 96-h LC50 of BP for 35 days (d) to investigate organ-specific responses. The results indicated significant damage to the exposed organs and showed damage in pillar cells and intraluminal debris in gill mucous cells. Moreover, fragmentation of intact muscle structures, intraluminal debris, and vascular necrosis were observed in exposed muscles. In conclusion, these results confirmed the histopathological changes in the gills and muscles of L. rohita caused by BP exposure, thereby confirming its risk to aquatic life.